A brackish to non-marine aquatic and terrestrial fossil assemblage with vertebrates from the lower Coniacian (Upper Cretaceous) Gosau Group of the Tiefengraben locality near St. Wolfgang im Salzkammergut, Austria. (November 2021) - Ősi, Attila; Szabó, Márton; Tóth, Emőke; Bodor, Emese; Lobitzer, Harald; Kvaček, Jiří; Svobodová, Marcela; Szente, István; Wagreich, Michael; Trabelsi, Khaled; Sames, Benjamin; Magyar, János; et al.
Abstract: The Turonian–Coniacian continental fossil record in Europe is scarce. Here we present a new fossil assemblage of early Coniacian age that was systematically collected from the coal-bearing Gosau Group of the Tiefengraben locality near St. Wolfgang, Austria. The diverse assemblage is composed of at least 60 taxa including sporomorphs and Normapolles-related pollen, seeds and leaves of angiosperms and gymnosperms, charophytes, gastropods, bivalves, ostracods, termites, fishes, crocodiles and dinosaurs. Concerning charophytes, ostracods, gastropods, crocodiles and dinosaurs, the discovered specimens either extend the temporal and spatial range of specific groups (in some cases as possible relict forms) or suggest the occurrence of new taxa. The discovered remains of algae, molluscs, ostracods, calcareous nannofossils and lepisosteid fish represent a mixed faunal assemblage from different palaeohabitats, from marginal marine to low salinity and freshwater or terrestrial environments. As Normapolles-related angiosperm plants dominate the flora with a relatively high number of dentate leaves, a slightly cooler microenvironment compared to other Turonian–Coniacian Central European localities is indicated. The characteristically grooved crocodylian teeth of Tiefengraben differ from the previously known Upper Cretaceous European crocodyliform teeth and suggest a more diverse crocodyliform fauna in the region. Dinosaurs are represented by teeth of at least three different theropods, the largest of which is referred here to as basal tetanurans. The fossil assemblage of this early Gosau Group occurrence is of great importance for our understanding of the continental floristic and faunistic composition of the western Tethyan archipelago during the Cenomanian–Campanian gap.